Poética do surrealismo: uma leitura de Campos de Carvalho - Pereira, Marcio Roberto [UNESP] (2010)
In this article we analyze how the character of the story-teller is build up as a fictional creation in the novel Vaca de nariz sutil (1961) by Walter Campos de Carvalho (1916-1998). We associated the building process of the narrator-character to the poetic of the surrealism, process which brings a fragmentary feature to the writer’s language, and reflects a search for some coherency in a given chaotic environment, wherein space itself becomes the role of a dialogue between identity and representation of the real in the construction of the narrative analyzed here.